CNTM-05. Left hemisphere gliomas induce a plastic bi-hemispheric language network further characterized by lobe specific glioma data. (12th November 2021) - Ramsey, Matthew; Tripathi, Shashwat; Saxena, Mohit; Tate, Matthew
Abstract: Primary brain tumors are among the most burdensome diagnoses patients can receive as they often carry with them externally obvious and significant detriments to motor and speech. The stroke model is severely limited by the inherent nature of the insult to the brain: binary, relatively instantaneous and defined by vascular boundaries. We instead have chosen to study glioma-induced neuroplasticity in patients with gliomas as presentation is over a significantly longer time course with a gradient of insult to language activation areas instead of immediate ablation. Chart review was conducted on 545 patients who completed fMRI imaging from 2013–2019 while completing 1+ of the following language tasks: antonyms, reading comprehension, rhyming, word generation and picture naming. A total of 117 patients' fMRI scans were included in the final analysis which entailed both a cluster-based analysis in FSL and a 34 gyral, mask-based analysis using FEATquery. Right hemisphere gliomas (RHG) were first established as a reliable control group by averaging anatomically significant voxels across all five language tasks (LT) yielding a core conserved network. Left hemisphere gliomas (LHG) were then directly compared to the RHG language tasks. We found LHG induced global reorganization of the conserved language network with little evidence for direct homologous recruitment of functional structures. Instead, a generalized right hemisphere recruitment is observed with 87% of non-zero masks shifting their laterality index to the right hemisphere. Furthermore, in each of the five LT, the LHG activates fewer total suprathreshold voxels in both the mask and cluster based analyses while having a higher peak intensity within the activated clusters. A preliminary analysis of frontal LHG compared to temporal LHG reveals increased contralateral recruitment in the frontal subgroup with more direct homologous recruitment. This nuanced understanding of existing mechanisms for neuroplasticity can aid in our future intentional manipulation for therapeutic benefit.